Gambaran Forgiveness pada Perempuan Korban Kekerasan dalam Rumah Tangga: Penelitian - Widya Susanti; Hasnida Hasnida; Josetta M.R. Tuapattinaja (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Domestic violence places women in complex psychological situations, often confronting them with the dilemma of staying in or leaving the relationship. One psychological response that emerges in this dynamic is forgiveness. This study aims to provide a descriptive profile of the levels and dimensions of forgiveness among women victims of domestic violence in North Sumatra. This study employed a quantitative approach with a descriptive design. Participants consisted of 210 women victims of domestic violence selected using quota nonprobability sampling. Data were collected using the Transgression Related Interpersonal Motivation Inventory (TRIM-18). The results indicated that, overall, victims exhibited a high level of forgiveness. However, dimensional analysis revealed that Avoidance Motivation had the highest mean score compared to Benevolence and Revenge. These findings suggest that most female victims of domestic violence may have begun to show acceptance of their partners' presence, despite having experienced painful treatment.